2014
DOI: 10.1186/1477-7819-12-226
|View full text |Cite
|
Sign up to set email alerts
|

High expression of thymosin beta 10 predicts poor prognosis for hepatocellular carcinoma after hepatectomy

Abstract: BackgroundThymosin beta 10 (Tbeta10) overexpression has been reported in a variety of human cancers. However, the role of Tbeta10 in hepatocellular carcinoma (HCC) remains unclear. The aim of the present study was to analyze Tbeta10 expression in tumor and matched non-tumorous tissues, and to assess its prognostic significance for HCC after hepatectomy.MethodsThe level of Tbeta10 mRNA and protein in tumor and matched non-tumorous tissues was evaluated in 26 fresh HCC cases by reverse transcription-polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(31 reference statements)
2
10
0
Order By: Relevance
“…Notably, thymosin beta 10 ( TMSB10 , z-score: 5.62, FDR: 0.00, Entrez ID: 9168) showed the largest difference in expression levels among statistically significant up-regulated DEGs. There is ample evidence suggesting that TMSB10 is one of the key regulators of malignancy and metastasis in various types of cancers and PM and DM are well-known for its association with malignancy [66,67]. Together, our results suggest that the acquired malignancy in PM and DM may be the result of the abnormal expression of TMSB10 .…”
Section: Discussionsupporting
confidence: 50%
“…Notably, thymosin beta 10 ( TMSB10 , z-score: 5.62, FDR: 0.00, Entrez ID: 9168) showed the largest difference in expression levels among statistically significant up-regulated DEGs. There is ample evidence suggesting that TMSB10 is one of the key regulators of malignancy and metastasis in various types of cancers and PM and DM are well-known for its association with malignancy [66,67]. Together, our results suggest that the acquired malignancy in PM and DM may be the result of the abnormal expression of TMSB10 .…”
Section: Discussionsupporting
confidence: 50%
“…Thymosin β10 (Tβ10) is a natural small molecule polypeptide that is widely distributed in many tissues with proven biological activities as an actin-sequestering protein involved in cell motility [28]. Tβ10 is associated with cell proliferation, cell morphology, cell migration and endocytosis, as well as participating in cytoskeleton assembly and presence [29].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarray analysis by Sulpice et al ( 29 ) demonstrated increased expression of COL4A1 in the stroma of ICC. Abnormal expression of TMSB10 may contribute to the malignant progression of HCC, and high expression of TMSB10 predicts poor prognosis in patients with HCC following hepatectomy ( 34 ). High TMSB10 expression is significantly associated with clinicopathological features, poor prognosis, and distant metastases in patients with breast cancer ( 35 ).…”
Section: Discussionmentioning
confidence: 99%